Measurement of software quality based on international standards - Zaporozhets, O.; Shtefan, N. (Radiotekhnika, 2021)
Quality is one of the factors that ensure the commercial success and safety of using the software. Quality is understood as conformity the explicit and implicit requirements of various stakeholders. It is necessary to ensure a joint understanding between developers and users, engineers need to understand the meaning of the concept of quality, characteristics and importance of quality for the developed or maintained software. Measurements are the basis for quality assurance. They are the main tool for managing the life cycle of software products, assessing the implementation of plans and monitoring. To quantify quality, it is necessary to measure the characteristics of the software. Standardization provides unification of requirements for quality, its measurement and assessment. The use of standards has many potential benefits for any organization, especially in key areas such as measuring the quality of software products, information and measurement systems. Recognized international standards organizations have published the ISO/IEC 25000 series of standards for systems and software quality requirements and evaluation (SQuaRE), which is gaining widespread practical application. The paper discusses a series of the SQuaRE international standards, analyzes the relationship between the quality model, quality characteristics, quality measures and a new concept, i.e., a quality measure element of the software, presents the measurement of quality based on these standards.